Effects of NPK, Amino Acid Liquid Organic Fertilizer on Maize (Zea mays L.) Growth And Yield - Muhamad Hisyam Adzikro; Alfu Laila; Andi Apriani Farmawaty; Endang Sulistyorini (Jurnal Agroekoteknologi Terapan, 2025)
Corn is one of the food crops cultivated in Indonesia. There has been a decline in corn production in Indonesia on a national scale and in Banten Province. Efforts are needed to increase sweet corn production, one of which is by using effective and efficient fertilizers. This research aims to determine the effect of applying amino acid Liquid Organic Fertilizer (POC) amino acids with different concentrations and different doses of single N,P,K on the growth and yield of sweet corn plants (Zea mays subsp. mays L.). This research was conducted using a Split-Plot Design, with amino acid POC concentration as the main plot, comprising four levels: control (K0), 2 mL/L/plot (K1), 4 mL/L/plot (K2), and 6 mL/L/plot (K3). Single dose of N,P,K as subplots with 3 levels: 100% dose (D1), 75% dose (D2), 50% dose (D3). The results showed that the concentration of amino acid POC 6mL/L/plot gave a significant effect on the parameters of cob weight, grain weight per cob, actual yield, and potential yield. The single N,P,K dose of 75% gave a real effect on the parameters of the weight of the cob, weight of the cob without the cob, weight of grains per cob, actual yield, and yield power. Keywords: NPK Fertilizer, Amino Acid Fertilizer, Sweet Corn